NADPH oxidase inhibition reduces tubular sodium transport and improves kidney oxygenation in diabetes - Persson, Patrik (American Physiological Society, 2012)
Sustained hyperglycemia is associated with increased oxidative stress resulting in decreased intrarenal oxygen tension (Po(2)) due to increased oxygen consumption (Qo(2)). Chronic blockade of the main superoxide radicals producing system, the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, normalizes Qo(2) by isolated proximal tubular cells (PTC) and reduces proteinuria in diabetes. The aim was to investigate the effects of acute NADPH oxidase inhibition on tubular Na(+) transport and kidney Po(2) in vivo. Glomerular filtration rate (GFR), renal blood flow (RBF), filtration fraction (FF), Na(+) excretion, fractional Li(+) excretion, and intrarenal Po(2) was measured in control and streptozotocin-diabetic rats during baseline and after acute NADPH oxidase inhibition using apocynin. The effects on tubular transporters were investigated using freshly isolated PTC. GFR was increased in diabetics compared with controls (2.2 ± 0.3 vs. 1.4 ± 0.1 ml·min(−1)·kidney(−1)). RBF was similar in both groups, resulting in increased FF in diabetics. Po(2) was reduced in cortex and medulla in diabetic kidneys compared with controls (34.4 ± 0.7 vs. 42.5 ± 1.2 mmHg and 15.7 ± 1.2 vs. 25.5 ± 2.3 mmHg, respectively). Na(+) excretion was increased in diabetics compared with controls (24.0 ± 4.7 vs. 9.0 ± 2.0 μm·min(−1)·kidney(−1)). In controls, all parameters were unaffected. However, apocynin increased Na(+) excretion (+112%) and decreased fractional lithium reabsorption (−10%) in diabetics, resulting in improved cortical (+14%) and medullary (+28%) Po(2). Qo(2) was higher in PTC isolated from diabetic rats compared with control. Apocynin, dimethylamiloride, and ouabain reduced Qo(2), but the effects of combining apocynin with either dimethylamiloride or ouabain were not additive. In conclusion, NADPH oxidase inhibition reduces tubular Na(+) transport and improves intrarenal Po(2) in diabetes.